Combined SPRi Sensor for Simultaneous Detection of Nitrate and Ammonium in Wastewater - Vráblová, Martina; Koutník, Ivan; Smutná, Kateřina; Marková, Dominika; Veverková, Nikola (Sensors (Basel, Switzerland), 2021)
Water pollution is a serious problem in modern society. Agriculture, being responsible for the discharge of agrochemicals, organic matter, or drug residues, produces a huge amount of wastewater. Aquaponics has the potential to reduce both water consumption and the impact of water pollution on fish farming and plant production. In the aquatic environment, inorganic nitrogen is mostly present in the form of nitrate and ammonium ions. Nitrate, as a final product of ammonia mineralization, is the most common chemical contaminant in aquifers around the world. For continuous monitoring of nitrogen compounds in wastewater, we propose a sensor for the simultaneous detection of nitrate and ammonium. A surface plasmon resonance imaging method with enzyme-mediated detection was used. Active layers of nitrate reductase and glutamine synthetase were created on the gold surface of a biochip and tested for the sensing of nitrate and ammonium in water from an aquaponic system. The proposed sensor was applied in water samples with a concentration of NO3- and NH4+ in a range between 24-780 mg·L-1 and 0.26-120 mg·L-1, respectively, with minimal pretreatment of a sample by its dilution with a buffer prior to contact on a biochip surface.
Keywords: nitrate; ammonium; aquaponics; surface plasmon resonance; wastewater; sensor